A comprehensive review on stir cast Al-SiC composite. (2020) - Nirala, Akhileshwar; Soren, S.; Kumar, N.; Dwivedi, V.K.; Kaushal, D.R.
Abstract: Aluminium matrix composite (AMC) is used widely in various industries such as aerospace, marine, automobile, power plant, house hold and substrate in electronics equipments etc due to excellent corrosion resistance, better weight to strength ratio and so on. There are several manufacturing technique to produce AMC but stir casting method used commonly due to less expensive and ability for mass production. There are some restrictions along with advantages i.e poor wet-ability of reinforcements with the molten Aluminium. Present study indicates briefly about manufacturing method, reinforcement's composition, size and shapes of the reinforcements in AMC. Further, the experiment tends to intricacy to taking part of quite a few parameters which influence the composite properties. Moreover, inadequate experimental data is existing because difficulties to reinforcements in composite. In this study, Aluminium metal matrix composites reinforced with SiC have been reviewed and the future scope presented briefly.